Analisis Studi Kelayakan Bisnis Mixue Ice Ceram & Tea Pada Aspek Aspek Pemasaran (Studi Kasus Mixue Pasar Bersih Cikarang) - Hanura Kalistha Putri; Maura Putri Alicia; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the business feasibility of Mixue Ice Cream & Tea at Pasar Bersih Cikarang from a marketing perspective. The research employs a descriptive method with a case study approach, gathering data through observation, interviews, and documentation. The analysis focuses on market segmentation, marketing strategies, marketing mix (4Ps), and customer satisfaction levels. The findings reveal that Mixue Ice Cream & Tea has significant market potential with clear segmentation, effective promotional strategies, and competitive pricing. Its strategic location and consistent product quality are key advantages in attracting customers. However, challenges exist in addressing market competition and maintaining customer loyalty. Therefore, the business is deemed feasible for further development with several recommendations for improvement in digital promotion and product innovation.